2007
DOI: 10.1016/j.ymben.2007.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux elucidation for large-scale models using 13C labeled isotopes

Abstract: A key consideration in metabolic engineering is the determination of fluxes of the metabolites within the cell. This determination provides an unambiguous description of metabolism before and/or after engineering interventions. Here, we present a computational framework that combines a constraintbased modeling framework with isotopic label tracing on a large-scale. When cells are fed a growth substrate with certain carbon positions labeled with 13 C, the distribution of this label in the intracellular metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 55 publications
0
110
0
Order By: Relevance
“…Theorem 3 of Isermann and Wiechert (2003)). We found that I PDO reduces the sum of all flux ranges (see Suthers et al, 2007) by about an order of magnitude. In summary, in this example we demonstrated that a preliminary implementation of OptMeas can exhaustively generate minimal measurement sets without requiring any measurement to be pre-selected in advance for small to medium-size metabolic models.…”
Section: Medium Scale Model For E Coli Metabolismmentioning
confidence: 73%
See 2 more Smart Citations
“…Theorem 3 of Isermann and Wiechert (2003)). We found that I PDO reduces the sum of all flux ranges (see Suthers et al, 2007) by about an order of magnitude. In summary, in this example we demonstrated that a preliminary implementation of OptMeas can exhaustively generate minimal measurement sets without requiring any measurement to be pre-selected in advance for small to medium-size metabolic models.…”
Section: Medium Scale Model For E Coli Metabolismmentioning
confidence: 73%
“…whereas the production and consumption terms for every isotopomer form of each intermediate metabolite must be equal to each other (see Suthers et al, 2007 for a derivation):…”
Section: Overview Of Mathematical Analysis For Mfamentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses typically utilize models containing approximately 100 reactions or less and most often, focus on incorporating nonlinear analysis to understand quantitative experimental data (e.g., isotopomer modeling). With the advancement of computational power and developed platforms, the networks that can be analyzed will grow in size 97 . Given that the results produced from analyses such as isotopomer modeling have been shown to be highly dependent on the content of a reduced model, the logical starting point for building such models is the E. coli GEM 97 .…”
Section: Phenotypic Functions: Gem Aided Assessmentmentioning
confidence: 99%
“…With the advancement of computational power and developed platforms, the networks that can be analyzed will grow in size 97 . Given that the results produced from analyses such as isotopomer modeling have been shown to be highly dependent on the content of a reduced model, the logical starting point for building such models is the E. coli GEM 97 . A number of noteworthy studies have been conducted with reduced models, but not detailed here as they are outside the scope of this review.…”
Section: Phenotypic Functions: Gem Aided Assessmentmentioning
confidence: 99%